2017
DOI: 10.1111/1911-3846.12294
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Risk Management and the Financial Reporting Process: The Experiences of Audit Committee Members, CFOs, and External Auditors

Abstract: The recent financial crisis has brought to the forefront the need for companies to effectively manage their risks. In this regard, one approach that has gained prominence is enterprise risk management (ERM). Importantly, little is known about the link between ERM and the financial reporting process. This link is critical, because it is imperative that financial reporting adequately depicts the financial status (e.g., valuations, estimates) and associated risks of a company as revealed by ERM. Additionally, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 44 publications
4
76
0
3
Order By: Relevance
“…Top management is also important (Arnold, Benford, Canada, & Sutton, 2011;Barton & MacArthur, 2015;Lundqvist, 2014;2015;Meidell & Kaarbøe, 2017;Tekathen & Dechow, 2013;Viscelli, Hermanson, & Beasley, 2017). Top management affects the formation of risk cultures because it influences the adoption of specific risk management procedures (Meidell & Kaarbøe, 2017), accountability within the organization (Cohen, Krishnamoorthy, & Wright, 2017), and organizational flexibility (Arnold et al, 2011;2015). Cohen et al (2017) found a strong relationship between ERM implementation and the financial reporting process based on a survey of CFOs, audit partners, and audit committee members of US companies.…”
Section: Factors That Promote or Obstruct The Introduction Of Ermmentioning
confidence: 99%
“…Top management is also important (Arnold, Benford, Canada, & Sutton, 2011;Barton & MacArthur, 2015;Lundqvist, 2014;2015;Meidell & Kaarbøe, 2017;Tekathen & Dechow, 2013;Viscelli, Hermanson, & Beasley, 2017). Top management affects the formation of risk cultures because it influences the adoption of specific risk management procedures (Meidell & Kaarbøe, 2017), accountability within the organization (Cohen, Krishnamoorthy, & Wright, 2017), and organizational flexibility (Arnold et al, 2011;2015). Cohen et al (2017) found a strong relationship between ERM implementation and the financial reporting process based on a survey of CFOs, audit partners, and audit committee members of US companies.…”
Section: Factors That Promote or Obstruct The Introduction Of Ermmentioning
confidence: 99%
“…Also, in the first decade of this century, and due to a number of scandals-similar to ENRON-there was ever-increasing attention for corporate governance and the role of operational risk management. This resulted in the first internationally used comprehensive corporate standard on risk management, the COSO Enterprise Risk Management Integrated Framework (2004) [42,43]. Enterprise Risk Management (ERM), similar to ORM in the military and aviation sectors, is the more organization-wide approach that is needed to cope with the complex realities and awareness of risks for the corporate world in the 21st century.…”
Section: Twenty-first Centurymentioning
confidence: 99%
“…Also, in the first decade of this century, and due to a number of scandals-similar to ENRONthere was ever-increasing attention for corporate governance and the role of operational risk management. This resulted in the first internationally used comprehensive corporate standard on risk management, the COSO Enterprise Risk Management Integrated Framework (2004) [42,43]. Enterprise Risk Management (ERM), similar to ORM in the military and aviation sectors, is the more organization-wide approach that is needed to cope with the complex realities and awareness of risks for the corporate world in the 21st century.…”
Section: Twenty-first Centurymentioning
confidence: 99%